Are there any prognostic prediction parameters (PPPs) in the treatment of the massive rotator cuff tear with latissimus dorsi transfer? Latissimus dorsi transfer in massive rotator cuff tears - Lehmann, L J; Cafaltzis, K; Hünnebeck, S; Moursy, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2013)
PURPOSE OF THE STUDY: Especially in such complex salvage procedures as latissimus dorsi transfer for irreparable rotator cuff tears there is a need for valid prognostic prediction parameters. Parameters such as osteoarthritis, acromiohumeral distance, subscapularis, or teres minor insufficiency are controversial. The aim of this study is to present our data and to evaluate the literature regarding such parameters. METHODS: Fifty-seven patients with a follow-up of 3 years (range, 18-72 months, n = 57) were selected for this study. Average age of patients at the time of surgery was 64.9 years. Patients were evaluated using the age and gender adjusted scoring system according to Constant and Murley score (CS). Standard radiography was attempted containing a true-ap, outlet, and axillary view. The acromio-humeral distance was measured in the true ap view. The grade of glenohumeral osteoarthritis and cuff tear arthropathy was detected using the classification of Hamada et al. Differences in CS were compared for each of the PPP. RESULTS: Mean Constant score increased significantly (p < 0.0001) 3 years postoperatively from initially 22.7 points to 66.0 points (adjusted CS 80.3%). We found a major difference in the Constant score in patients with or without previous surgery (80.4% vs, 65.2%). CONCLUSION: Latissimus dorsi transfer is an excellent option in the treatment of irreparable postero-superior tears of the rotator cuff in well-selected patients. The literature remains ambiguous with regard to valid prognostic predictive parameters for complex salvage procedures, owing to the consistent use of small study samples. Thus, there is an overwhelming need for a multicenter study.
Keywords: Humans; lidé středního věku; přenos šlachy; Female; Aged; dospělí; výsledek terapie; senioři; lidé; Rotator Cuff Injuries; Tendon Transfer; Rotator Cuff; rotátorová manžeta; Adult; ženské pohlaví; Male; Middle Aged; prognóza; Treatment Outcome; mužské pohlaví; poranění rotátorové manžety; Prognosis